CPP Transport Properties of Ni/Ru and Co90Fe10/Cu Interfaces - Kim, Do Kyun; Lee, Yeon Sub; Nguyen, Hoang Yen Thi; Acharyya, Rakhi; Loloee, Reza; Shin, Kyung-Ho; Kim, Young Keun; Min, Byoung-Chul; Pratt, W. P., Jr.; Bass, Jack (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2010)
Using current-perpendicular-to-plane (CPP) magnetoresistance measurements, we derive values of twice the enhanced interface resistance, 2AR(F/N)*, and the interface scattering asymmetry, gamma(F/N), for the ferromagnetic/non-magnetic (F/N) pairs Ni/Ru and Co90Fe10/Cu. For Ni/Ru, we find 2AR(Ni/Ru)* = 1.7(-0.3)(+0.4) f Omega m(2), similar to the value for Fe/Cr, but we estimate vertical bar gamma(Ni/Ru)vertical bar = 0.15 +/- 0.03, much smaller than the value for Fe/Cr or the asymmetry found for Ni(Ru) alloys. For Co90Fe10 we find 2AR(CoFe/Cu)* = 1.1 +/- 0.2 and gamma(CoFe/Cu) = 0.8 +/- 0.1, both similar to the values for Co/Cu.